Climate Change Mitigation in Context to Telangana (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Climate change poses a significant challenge to semi-arid regions such as Telangana, India, where increasing temperatures, erratic rainfall, and rapid urban expansion intensify environmental stress. This study presents a comprehensive and analytically enriched assessment of climate change mitigation strategies in Telangana, focusing on renewable energy, afforestation, sustainable agriculture, and urban climate interventions.The research integrates secondary datasets with quantitative trend analysis, including percentage change, variability indices, and comparative sectoral evaluation. Results reveal a 2.8°C rise in average temperature (2000–2025) and high rainfall variability with fluctuations between 760 mm and 950 mm, indicating climatic instability. Mitigation initiatives such as the Cool Roof Policy, solar energy expansion, and afforestation programs demonstrate measurable impacts, including reduced energy consumption (up to 15–20%) and increased carbon sequestration potential.However, effectiveness varies across sectors due to implementation gaps, limited monitoring, and socio-economic constraints. This study introduces a performance-based evaluation framework using measurable indicators such as emission reduction potential, energy savings, and resilience capacity. The findings highlight the need for integrated policy enforcement, technological innovation, and stakeholder participation.The study contributes to regional climate policy discourse and provides a replicable framework for semi-arid regions.